1987
DOI: 10.1113/jphysiol.1987.sp016373
|View full text |Cite
|
Sign up to set email alerts
|

The effect of splanchnic nerve stimulation on adrenocortical activity in conscious calves.

Abstract: SUMMARY1. Right adrenal and various cardiovascular responses to stimulation of the peripheral end of the right splanchnic nerve have been investigated in the presence and absence of exogenous adrenocorticotrophin, ACTH1-24, (5 ng min' kg-'). The adrenal-clamp technique was employed in conscious calves in which the pituitary stalk had been cauterized 3-4 days previously.2. The i.v. infusion of ACTHl-24 increased mean plasma ACTH concentration by about 1200 pg/ml and mean right adrenal cortisol output by about 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 22 publications
3
50
0
1
Order By: Relevance
“…One such is the innervation to the gland, which exerts an important modulating influence (Engeland, A. V. EDWARDS AND C. T. JONES Byrnes, Presnell, & Gann, 1981;Wood, Shinsako & Dallman, 1982a;Wood, Shinsako, Keil, Ramsay & Dallman, 1982b;Dempsher & Gann, 1983;Engeland, Lilly & Gann, 1985;Edwards, Jones & Bloom, 1986). More recently it has been established that splanchnic nerve stimulation enhances the steroidogenic response of the adrenal cortex to ACTH (Edwards & Jones, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…One such is the innervation to the gland, which exerts an important modulating influence (Engeland, A. V. EDWARDS AND C. T. JONES Byrnes, Presnell, & Gann, 1981;Wood, Shinsako & Dallman, 1982a;Wood, Shinsako, Keil, Ramsay & Dallman, 1982b;Dempsher & Gann, 1983;Engeland, Lilly & Gann, 1985;Edwards, Jones & Bloom, 1986). More recently it has been established that splanchnic nerve stimulation enhances the steroidogenic response of the adrenal cortex to ACTH (Edwards & Jones, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…[Met5]-enkephalin was measured by a specific radioimmunoassay as described previously (Edwards, Hansell & Jones, 1986;Edwards & Jones, 1987 …”
Section: Experiments Proceduresmentioning
confidence: 99%
“…In addition, although it is known that the ovine placenta is not permeable to ACTH (43) and that maternal cortisol is metabolized in the placenta by the enzyme 11 ␤-hydroxysteroid dehydrogenase (44), the absence of any significant alterations in maternal plasma ACTH and cortisol Previous studies have suggested a role for the splanchnic sympathetic nerves innervating the adrenal gland in the steroidogenic response to stress, because stimulation of the splanchnic nerves doubled and section of these nerves halved the increase in plasma concentrations of cortisol in response to exogenous ACTH in conscious, hypophysectomized calves (45,46) and lambs (47). Similarly, the increase in plasma concentrations of cortisol in response to acute hypoxemia were attenuated or completely abolished in carotid chemodenervated sheep (33) and llama (48) fetuses, respectively.…”
Section: Dexamethasone and The Materno-fetal Hpa Axismentioning
confidence: 99%